Of Stewardship, Suffering and the “Slippery Slope”: A Vattimian Analysis of the Sanctity of Life Ethos in Canada (1972–2005) - Chambers, Stuart (Université d'Ottawa / University of Ottawa, 2011)
This dissertation examines from a Vattimian perspective the challenge that euthanasia and assisted suicide posed to the sanctity of life ethos in Canada from 1972–2005. Gianni Vattimo’s central themes—metaphysics (absolute values), “event of being” (lived experiences that call absolute values into question), and passive-reactive nihilism (the use of “masks” or “disguises” to prevent the dissolution of metaphysics)—are pivotal to understanding the way religious and secular beliefs are interwoven within ethical, medical, legal and political discourses in Canada. Vattimo’s philosophico-ethical approach was specifically chosen because as a theoretical tool, it helps to illuminate the presence, weakening, and resilience of metaphysics in discourses surrounding an intentionally hastened death. To demonstrate how Vattimo’s major themes apply empirically to the research, a social constructionist approach was adopted in the form of a discourse analysis. Particular emphasis was placed on an examination of the three most important cases of death and dying in Canada, namely, Nancy B., Sue Rodriguez and Robert Latimer. The bulk of the evidence suggests that when these “events of being” challenged the sanctity doctrine as the ultimate foundation for life-terminating decisions, ethical, medical, legal and political discourses converged to promote three normative positions or authorizing discourses used in the tradition of Christian ethics: (1) stewardship—the view that since life is a “loan from God,” sacred, and of infinite worth, death cannot be intentionally hastened (“nature must take its course”); (2) value in prolonged suffering—the view that since suffering possesses transcendent meaning or purpose, its prolongation is justified in individual circumstances; and (3) the “slippery slope”—the view that any weakening of the sanctity of life ethos inevitably harms or threatens the community. Generally speaking, religious and secular advocates of the sanctity of life ethos reacted similarly in cases involving an intentionally hastened death. In other words, both the religious and the secular embraced metaphysics (absolute values), condoned and rationalized the prolongation of suffering, and relied on the “slippery slope” as a “mask” to maintain the sanctity of human life as first principle. The research strongly suggests that Canada is still significantly indebted to Christian notions when it comes to discussions surrounding the decriminalization of euthanasia and assisted suicide.
Keywords: sanctity of life ethos; quality of life ethos; euthanasia; assisted suicide; stewardship; suffering; slippery slope; metaphysics; event of being; passive-reactive nihilism; Nancy B.; Sue Rodriguez; Robert Latimer; religious attitudes; Christian; metaphysicians; Vattimian postmodernists